Pregnant women with bipolar disorder who have a history of childhood maltreatment: Intergenerational effects of trauma on fetal neurodevelopment and birth outcomes. (28th March 2022) - Babineau, Vanessa; McCormack, Clare A.; Feng, Tianshu; Lee, Seonjoo; Berry, Obianuju; Knight, Bettina T.; Newport, Jeffrey D.; Stowe, Zachary N.; Monk, Catherine
Abstract: Objectives: Intergenerational transmission of trauma occurs when the effects of childhood maltreatment (CM) influence the next generation's development and health; prenatal programming via maternal mood symptoms is a potential pathway. CM is a risk factor for bipolar disorder which is present in 1.8% of pregnant women. Mood symptoms are likely to increase during pregnancy, particularly for those with a history of CM. We examined whether there was evidence for intergenerational transmission of trauma in utero in this population, and whether maternal mood was a transmission pathway. Methods: CM and maternal mood were self‐reported by N = 82 pregnant women in treatment for bipolar disorder. Fetal heart rate variability (FHRV) was measured at 24, 30, and 36 weeks' gestation. Gestational age at birth and birth weight were obtained from medical charts. Results: A cluster analysis yielded two groups, Symptom+ (18.29%) and Euthymic (81.71%), who differed on severe mood symptoms ( p < 0.001) but not on medication use. The Symptom+ group had more CM exposures ( p < 0.001), a trend of lower FHRV ( p = 0.077), and greater birth complications (33.3% vs. 6.07% born preterm p < 0.01). Maternal prenatal mood mediated the association between maternal CM and birth weight in both sexes and at trend level for gestational age at birth in females. Conclusions: This is the first study to identify intergenerational effects of maternal CM prior to postnatal influences in a sample of pregnant women with bipolar disorder. These findings underscore the potential enduring impact of CM for women with severe psychiatric illness and their children.